Pengaruh Loyalitas, Pendidikan dan Pelatihan Pegawai terhadap Promosi Jabatan pada Kantor Sekretariat Daerah Kabupaten Nagan Raya - Susanto, Dimas Bagus; Hamzali, Said (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of the simultaneous influence of work loyalty, education and training on job promotion at the Regional Secretariat Office of Nagan Raya Regency, to determine the partial effect of work loyalty on promotion of the Regional Secretariat Office of Nagan Raya Regency, to determine the partial effect of education. on the promotion of the Nagan Raya Regency Regional Secretariat Office, to determine the partial effect of training on the promotion of the Nagan Raya Regency Regional Secretariat Office.This research was conducted at the Regional Secretariat Office of Nagan Raya Regency, while the object of this research is about work loyalty, education, training and promotion with 72 respondents. The data that has met the validity test, reliability test and classical assumption test are processed to produce the following regression equation: Y = 0.486X1 + 0.290X2 + 0.347X3 + 1. The results showed that work loyalty, education and work discipline together had a significant effect on promotion of the Regional Secretariat Office of Nagan Raya Regency with Fcount > Ftable (72.174 > 2.672) at a significance level of 0.0001, then the results of the study also proved that work loyalty individually significantly influence the promotion of the Office of the Regional Secretariat of Nagan Raya Regency with a regression coefficient of 0.486.The results also prove that individual participatory education has a significant effect on promotion of the Nagan Raya Regency Regional Secretariat Office with a regression coefficient value of 0.290 and individual training has a significant effect on promotion of the Nagan Raya Regency Regional Secretariat Office with a regression coefficient value of 0.347. After conducting this research, the Regional Secretariat Office of Nagan Raya Regency should be able to further improve services to the community, so that customers become satisfied with the services provided.